The mediating role of job satisfaction related to nurse-nurse collaboration and turnover intention - Mustafa Şahin; Gülfer Bektaş; Mustafa Nal; Ahmet Can Küçükkurt (BMC Nursing)
Abstract Background In recent years, nurses’ turnover has become a major problem, especially in underdeveloped and developing countries. This research aims to reveal the mediating role of job satisfaction in the effect of nurse-nurse collaboration on turnover intention. Methods This study is a quantitative, descriptive, cross-sectional study. This study was conducted in three private hospitals within a healthcare group in Turkey. The research was conducted with the participation of 534 nurses. These data were analyzed using moderated mediation regressions with the SPSS PROCESS macro. Results Nurse-nurse collaboration had a significant effect on turnover intention and job satisfaction. Job satisfaction had a significant effect on turnover intention. The mediating effect of job satisfaction on the effect of nurse-nurse collaboration on turnover intention was significant. Conclusions Our findings show that nurse-nurse collaboration and job satisfaction are important for reducing turnover intention. It shows that job satisfaction is an important mediating variable in the effect of nurse-nurse collaboration on reducing turnover intention. Clinical trial number Not applicable